2022
DOI: 10.1186/s12886-022-02699-y
|View full text |Cite
|
Sign up to set email alerts
|

Buccal mucosal membrane graft for correction of cicatricial lower eyelid retraction

Abstract: Background To evaluate the outcomes of a surgical technique using buccal mucosal membrane graft for correction of cicatricial lower eyelid retraction. Methods Twelve patients with unilateral cicatricial lower eyelid retraction were enrolled in the study. All patients underwent a four-step surgical technique consisted of release of scars, midface lift, transfer of buccal mucosal membrane to posterior lamella as spacer graft, and canthal tightening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The literature reported that a variety of grafts could be used as spacers for posterior lamellae in the lower lid, and it is proposed that grafts can be divided into 4 groups: autografts, allografts, xenografts, and synthetic grafts, including the hard palate, tarsal bone, nasal septal cartilage, human cadaver acellular dermis, acellular porcine-derived membrane, and high-density polyethylene 8–16 . The decision in the selection of the best graft is associated with its long-term stability, complications at recipient and donor sites, and cosmesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reported that a variety of grafts could be used as spacers for posterior lamellae in the lower lid, and it is proposed that grafts can be divided into 4 groups: autografts, allografts, xenografts, and synthetic grafts, including the hard palate, tarsal bone, nasal septal cartilage, human cadaver acellular dermis, acellular porcine-derived membrane, and high-density polyethylene 8–16 . The decision in the selection of the best graft is associated with its long-term stability, complications at recipient and donor sites, and cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple surgical techniques have been reported successively, from the relatively simple surgical approaches, such as tarsotomy and release of scar limiting upward mobilization of the lid, to more complex procedures, such as lengthening of the middle and posterior lamellas, using spacer grafts 5–7 . Graft materials may include hard palate, buccal mucosa, donor sclera, ear cartilage, nasal cartilage, alloplastic materials, and acellular porcine dermis 8–15 …”
mentioning
confidence: 99%